Linear Parameter Varying Path Tracking Control for Over-Actuated Electric Vehicles - Gimondi, Alex; Corno, Matteo; Savaresi, Sergio Matteo (Frontiers in Control Engineering, 2021)
This paper discusses a multi-layer linear parameter varying path tracking controller for autonomous full electric vehicles with 4 wheel drive. Many approaches for path tracking are present in the literature, but the majority of them utilize only the steering wheel. Nowadays, the massive introduction of electric vehicles opens new opportunities for vehicle dynamics control; multiple electric motors, via differential torque, offer an alternative way to influence vehicle motion. The multi-layer structure, managing separately steering wheel and electric motors, permits the exploitation of pre-existing control systems and maintains a straightforward tuning process. Furthermore, the robustness of the path tracking controller is enhanced by introducing tyre nonlinearities. Linear parameter varying models offer a direct way to incorporate tyre characteristics in the design process. Exploiting Hinf technique the scheduled controller can be seamlessly synthesised. The proposed strategy has been compared in simulation to a benchmark integrated, i.e. a unique controller that manages all the actuators, approach. During double lance changes beyond the vehicle limits, the multi-layer controller guarantees stability and excellent tracking with an average error of 12 cm and 24 cm on high and low grip respectively.